Sensibilidade ao contraste espacial de luminância e discriminação de cores na esquizofrenia: qual o papel dos antipsicóticos? - Fernandes, Thiago Monteiro de Paiva (2017)
Schizophrenia is a complex disorder with heterogeneous pathophysiology, affecting about 1% of the world population. Whereas there are several studies investigating cognition and behavior, basic visual function are poorly studied, even being important markers for the prognosis of the disorder. Here we investigated the visual processing and its link with antipsychotics drugs in schizophrenia, evaluating the spatial luminance contrast sensitivity and the color discrimination. Data were obtained from 45 participants, a group of schizophrenic using typical medication (n = 15), a group using atypical medication (n = 15) and a group of healthy individuals (n = 15), aged between 20 to 45 years. Participants were matched for level of education, age and gender. Vertical sine-wave gratins ranging from 0.2 to 16 cycles per degree were used for contrast sensitivity function assessment (CSF), and the Lanthony D15d (D15d) and Cambridge Colour Test (CCT) were used for assessing color vision. All subjects had undergone ophthalmologic examinations in the last two years, being free of observable eye diseases. The results indicated that the group of schizophrenic patients presented lower performance in comparison to the control group (p < .05) for all procedures. Pairwise comparisons showed that the group using typical antipsychotics had the lowest performance (p < .001), followed by the group using atypical antipsychotics (p < .01). These results suggest that schizophrenia and antipsychotics interacts with visual processing. Our study highlights the importance of understanding the diffuse effects of antipsychotic medication on visual processing.